Lowering serum homocysteine in H-type hypertensive patients with atrial fibrillation after radiofrequency catheter ablation to prevent atrial fibrillation recurrence - Dong, Youzheng; Huang, Ting; Zhai, Zhenyu; Dong, Quanbin; Xia, Zhen; Xia, Zirong; Yu, Jianhua; Jiang, Xinghua; Hong, Kui; Wu, Yanqing; Cheng, Xiaoshu; Li, Juxiang (Frontiers in Nutrition, 2022)
Background: Prior investigation revealed that elevated serum total homocysteine (tHcy) are strongly correlated with atrial fibrillation (AF) recurrence. Herein, the goal of this study was to elucidate whether folic acid (FA) treatment reduced AF recurrence following radiofrequency catheter ablation (RFCA). Methods: To conduct this retrospective research, we included consecutive H-type hypertensive AF patients, who were treated with first RFCA, between January 2010 and January 2022. We assessed the AF recurrence risk between patients who were taking 10 mg enalapril and 0.8 mg FA in a single-pill combination (enalapril–FA) daily and those who were taking a pill of 10 mg enalapril only. Outcomes were compared using the propensity-score matched analysis. Cox regression model was employed for the evaluation of AF recurrence events. Results: Out of 2714 patients, 645 patients receiving enalapril and 282 patients receiving enalapril-FA were included for analysis. Following propensity score matching, 239 patients remained in each group. These patients were followed-up for a median of 379 (137-596) days, and revealed that the enalapril-FA patients had drastically reduced AF recurrence, compared to the enalapril patients (adjusted hazard ratio (HR), 0.68; 95% confidence interval [CI], 0.48 to0.97; P=0.029). Apart from this, no interactions were detected in the subgroup analysis. Conclusion: In H-type hypertensive AF patients who were treated with first RFCA, FA supplementation was correlated with a reduced AF recurrence risk.